Effects of Neutralization, Decoloration, and Deodorization on Polycyclic Aromatic Hydrocarbons during Laboratory-Scale Oil Refining Process - Yuxiang Ma; Longkai Shi; Yulan Liu; Qiyu Lu (Journal of Chemistry)
The influence of technological operations during oil refining process on polycyclic aromatic hydrocarbons (PAHs) in neutralized, bleached, and deodorized oils was investigated on the basis of laboratory-scale study. Under the best experimental conditions, benzo[a]pyrene decreased by 85.1%, 99.7%, and 40.8% in neutralized, bleached, and deodorized oils, respectively. Total of 16 analytes decreased by 55.7%, 87.5%, and 47.7%, respectively. Bleaching with activated charcoal was the most efficient procedure to reduce PAHs in crude oil. Neutralization had a modest influence on sixteen analytes; however, deodorization was only responsible for a slight decrease in the light PAHs and heavy PAHs contents. Data obtained in this study suggest that the use of activated carbon during oil refining process is highly recommended; moreover, these results provide a useful guidance for oil refining plant to reduce security risk and ensure the quality of the vegetable oil products.